Children of the ‘Now’: Dispelling Some Neoliberal Assumptions in Christian Religious Education - Hyde, Brendan (Religious education, 2023)
That childhood is important in and of itself is a key ideal that should shape religious education and childhood religious formation more broadly. However, the neoliberal values of western society have influenced religious education, such that we tend to focus on who the child is becoming in terms of a future potential, instead of who the child is now. This essay questions this practice, calling on religious educators to honor children’s being and their ontological spirituality.